The Impact of the Virus on the Investment Climate of Uzbekistan and in General (International Journal of Psychosocial Rehabilitation, 2020)
As it is known in the world today, almost all countries are susceptible to the Covid-19 virus. This has affected not only people's health, but also the economy, especially investment. The threat of the virus has driven the world's economy into a corner. This is no longer a question of investing for profit. Businesses are trying to stay afloat. People have become more United and help each other in any way they can. Investors in major countries invest in other countries to help people in need. The article describes the risks of investments and analyzes them. Some recommendations are suggested for extracting minimal losses in such a difficult situation.